Emergence of Multidrug-Resistant Campylobacter jejuni in a Common Variable Immunodeficiency Patient: Evolution of Resistance Under the Selective Antibiotic Pressure - Tajana Juzbašić; Nataša Andrijašević; Ivana Ferenčak; Dragan Jurić; Silvija Šoprek; Vlatka Poje Janeš; Ljiljana Žmak; Arjana Tambić Andrašević; Ana Gverić Grginić (Tropical Medicine and Infectious Disease)
Campylobacter jejuni is a leading cause of bacterial gastroenteritis worldwide which usually presents as mild, and self-limiting disease in immunocompetent individuals. However, in immunocompromised patients, such as those with common variable immunodeficiency, C. jejuni can cause severe recurrent infections requiring antibiotic treatment. Our study reports a case of a 37-year-old male patient with CVID, who had multiple episodes of C. jejuni intestinal infections over a 3.5-year period. A total of 27 stool samples were collected and analyzed between December 2020 and July 2024 during acute febrile diarrheal episodes, with C. jejuni isolated in 15 samples. Antimicrobial susceptibility testing (AST) during the course of the disease revealed three different antimicrobial resistance profiles including multi-drug-resistant phenotype. Whole genome sequencing was performed on three representative isolates, all identified as MLST type 367, ST-257 complex, with minimal genetic divergence, indicating a clonal origin. Genes and point mutations conferring resistance to macrolides, fluoroquinolones, beta-lactams, and tetracycline were identified in different C. jejuni isolates, along with key virulence factors linked to adherence, invasion, motility, and immune evasion. The genetic analysis of macrolide phenotypic resistance revealed different resistance mechanisms. Genotypic and phenotypic analyses of the same C. jejuni clone from single patient, and identified multidrug resistance pattern, present the first documented case of in vivo resistance development of C. jejuni in Croatia. This case highlights the role of prolonged antibiotic pressure in driving resistance evolution and underscores the need for careful antimicrobial stewardship and genomic monitoring in immunocompromised patients. Further research is needed to correlate phenotypic resistance with genetic determinants in Campylobacter spp.